Abnormalities in red blood cell production and pathogenesis of anemia in the progression of rock bream iridovirus (RBIV) - Soo-Jin Kim; Jayeon Cheon; Mi Young Cho; Sung-Ju Jung; Myung-Hwa Jung (Virus Research, 2024)
Rock bream iridovirus (RBIV), belonging to Megalocytivirus, causes severe mortality in rock bream. Almost all deaths associated with RBIV are accompanied by splenic enlargement and anemia. Although red blood cells (RBCs) are involved in the immune response against viral infections, their involvement in rock bream has not yet been studied in terms of the immune response against RBIV. In this study, the viral replication patterns, blood characteristics and anemia-related factors were evaluated in rock bream post RBIV infection. The virus-infected RBCs of rock bream demonstrated similarities in the expression levels of hemoglobins (HGB) (α and β), cytokine-dependent hematopoietic cell linker (CLNK) and hematopoietic transcription factor GATA (GATA), with significantly decreasing levels from 4 days post infection (dpi) to 17 (dpi), when the viral replication was at its peak. This suggests that the expression of blood-related genes is inadequate for HGB synthesis and RBC production, thereby causing anemia leading to death. Moreover, the levels of complete blood cell count (CBC) indicators, such as RBCs, HGB and hematocrit (HCT), significantly decreased from 10 to 17 dpi. This phenomenon suggests that blood-related gene expression and/or RBC-, HGB- and HCT-related levels are critical factors in RBIV-induced anemia and disease progression. These results highlight the significance of blood-mediated immune responses against RBIV infection in rock bream. Understanding blood-related gene levels to identify blood-related immune response interactions in rock bream will be useful for development of future strategies in controlling RBIV diseases in rock bream.